2016
DOI: 10.1186/s13104-016-1962-1
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision syndrome among computer office workers in a developing country: an evaluation of prevalence and risk factors

Abstract: BackgroundComputer vision syndrome (CVS) is a group of visual symptoms experienced in relation to the use of computers. Nearly 60 million people suffer from CVS globally, resulting in reduced productivity at work and reduced quality of life of the computer worker. The present study aims to describe the prevalence of CVS and its associated factors among a nationally-representative sample of Sri Lankan computer workers.MethodsTwo thousand five hundred computer office workers were invited for the study from all n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
289
8
42

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(438 citation statements)
references
References 18 publications
44
289
8
42
Order By: Relevance
“…Studies done by Shantakumari et al and several others also reported headache as the most common or disturbing symptom following the use of digital devices. 10,14,18,19,22 Similar to the present study results, the other common symptoms which included tired eyes, watery eyes, dry eyes and back pain were also found by Moldovan et al among Romanian computer using medical students. 23 Blurred vision was the most common symptom reported by Lakachew et al among bank workers and Dessie et al among computer users in Ethiopia.…”
Section: Symptomssupporting
confidence: 89%
See 2 more Smart Citations
“…Studies done by Shantakumari et al and several others also reported headache as the most common or disturbing symptom following the use of digital devices. 10,14,18,19,22 Similar to the present study results, the other common symptoms which included tired eyes, watery eyes, dry eyes and back pain were also found by Moldovan et al among Romanian computer using medical students. 23 Blurred vision was the most common symptom reported by Lakachew et al among bank workers and Dessie et al among computer users in Ethiopia.…”
Section: Symptomssupporting
confidence: 89%
“…17 Duration of digital screen time was shown be significantly associated in several studies. 9,10,13,19,21,29,30 Better ergonomic practices' knowledge and practicing the preventive measures is significantly associated with DES symptoms as shown in studies done by Ranasinghe et al, Agarwal et al and Shantakumari et al 11,14,18 Contact lens wearers are more likely to suffer DES than non-lens wearers according to Tauste et al 31 Critical fusion frequency decreased significantly after visual task according to Lin et al who studied the effects reflected glare and visual field lighting. 32…”
Section: Factors Associated With Desmentioning
confidence: 98%
See 1 more Smart Citation
“…In present study, 66.3% subjects were suffering from aesthenopic symptoms during or after work on computer.In a comprehensive national survey on the prevalence of CVS in computer office workers from a South Asian country by Ranasinghe et al, the 1 year prevalence of CVS was 67.4 % [5]. Previous studies on CVS from Malaysia (68.1 %) and Nigeria (74.0 %) have demonstrated similar results [6,7].…”
Section: Discussionmentioning
confidence: 77%
“…In fact, this number annually grows at a rate going from 10% to 50% [1]. Every year, between 11% and 14,1% of employees do not go to work because of neck pain [1,5]. This project suggests designing a new tool for improving detection and prevention of MSD in real situation.…”
Section: Introductionmentioning
confidence: 99%